Is Islamic Higher Education Ready to Become an Entrepreneurial University? - Sonita, Era; Febrimansyah, Rudi; Henmaidi, Henmaidi; Nofialdi, Nofialdi; Fauziah, Suci (Universitas Pendidikan Ganesha, 2025)
This study explores the transformation of entrepreneurship in Islamic State Universities in Indonesia with a case study of Islamic State Universities in West Sumatra, UIN Imam Bonjol Padang UIN, UIN Sjech M. Djamil Djambek Bukittinggi and UIN Ahmad Yunus Batusangkar are Islamic State Universities in West Sumatra that have prepared themselves to face changes in the concept of higher education and shifts in the expectations of society and industry towards the role of universities in the economy. Respondents in this study were leaders, lecturers of entrepreneurship courses, researchers focused on entrepreneurship, students, and business development center units. This study aims to determine how big the gap is between performance and expectations from the implementation of the entrepreneurial university ecosystem using the Importance Performance Analysis (IPA) method. The European Commission and OECD entrepreneurial university framework was applied for data analysis. The Cartesian diagram in the Importance Performance Analysis (IPA), shows that five aspects must be the focus of Islamic State Universities in West Sumatra, consisting of UIN Padang, UIN Bukittinggi, and UIN Batusangkar, which must be improved in their implementation. The five aspects are: 1) leadership and governance; 2) organizational capacity, human resources, and incentives; 3) development of entrepreneurship in learning and teaching; 4) university-industry/external relations in knowledge exchange; 5) entrepreneurial universities as international institutions.